2008
DOI: 10.1097/01.hp.0000314807.29873.71
|View full text |Cite
|
Sign up to set email alerts
|

DETERMINATION OF 240Pu/239Pu ISOTOPIC RATIOS IN HUMAN TISSUES COLLECTED FROM AREAS AROUND THE SEMIPALATINSK NUCLEAR TEST SITE BY SECTOR-FIELD HIGH RESOLUTION ICP-MS

Abstract: Information on the 240Pu/239Pu isotope ratios in human tissues for people living around the Semipalatinsk Nuclear Test Site (SNTS) was deduced from 9 sets of soft tissues and bones, and 23 other bone samples obtained by autopsy. Plutonium was radiochemically separated and purified, and plutonium isotopes (239Pu and 240Pu) were determined by sector-field high resolution inductively coupled plasma-mass spectrometry. For most of the tissue samples from the former nine subjects, low 240Pu/239Pu isotope ratios were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
2
1
Order By: Relevance
“…The 239 Pu/ 240 Pu ratio was also determined by ICP-SFMS in different tissues of persons living close to the Semipalatinsk nuclear test site. 313 Pu concentrations in lung, liver and bone were found not to be elevated compared to values from other areas.…”
Section: Elemental Analyses Of Body Tissues and Body Fluidscontrasting
confidence: 58%
“…The 239 Pu/ 240 Pu ratio was also determined by ICP-SFMS in different tissues of persons living close to the Semipalatinsk nuclear test site. 313 Pu concentrations in lung, liver and bone were found not to be elevated compared to values from other areas.…”
Section: Elemental Analyses Of Body Tissues and Body Fluidscontrasting
confidence: 58%
“…In addition, prior to use the 242 Pu tracer solution, the interference and down-mass tailing of 242 Pu tracer (including 242 Pu itself and the other impurities) on m/z 239, 240 and 242 resulting from polyatomic ions of lead isotopes such as 204 Pb ( 204 Pb 35 Cl þ , 204 Pb 36 Ar þ ), 206 Pb ( 206 Pb 36 Ar þ ) and 207 Pb ( 207 Pb 35 Cl þ ) was checked by the blank test. Details of the operating conditions were described in another paper (Yamamoto et al, 2008). To confirm the accuracy of the determination, 239þ240 Pu concentration and 240 Pu/ 239 Pu atomic ratio were analyzed for certified reference materials of IAEA-135 (Irish Sea sediment) and IAEA-SOIL-6.…”
Section: Pu/ 239 Pu Atom Ratio Measurement By Sf-icp-msmentioning
confidence: 99%
“…Higher values were obtained at the Semipalatinsk test site (STS) during the 2000's, indicating an effect of the test site fallout in the plutonium body burden of the population (Yamamoto et al, 2006). Using ICP-MS, (Yamamoto et al, 2008) found a significantly lower 240 Pu/ 239 Pu isotopic ratio of 0.125 in autopsy tissues (bone) of individuals from the STS, confirming the influence of the STS fallout on plutonium incorporation. There were too few bone ash samples in our study to separate individuals from different regions, especially the ones potentially affected by the Swiss NPPs.…”
Section: Plutonium In Bonesmentioning
confidence: 79%